The Role of Bio-energy with Carbon Capture and Storage in Meeting the Climate Mitigation Challenge: A Whole System Perspective. (July 2017) - Mander, Sarah; Anderson, Kevin; Larkin, Alice; Gough, Clair; Vaughan, Naomi
Abstract: This paper explores the role and implications of bio-energy with carbon capture and storage (BECCS) for addressing the climate change mitigation challenge. Framed within the context of the latest emissions budgets, and their associated uncertainty, we present a summary of the contribution of BECCS within the Integrated Assessment Model (IAM) scenarios used by the climate change community. Within this discussion we seek to shed light on two important areas. Firstly, that BECCS is a central, but often hidden element of many of the modelling work that underpins climate policy from the global to the national scale. The second area we address are the assumptions for BECCS embedded within IAM models, and the wider system consequences of these implied levels of deployment. In light of these challenges, we question whether BECCS can deliver what is anticipated of it within existing climate change policy.